Delhivery: Fulfilling E-commerce Delivery. Issue 2 (September 2022) - Parameswar, Nakul; Dhir, Sanjay
Delhivery started in 2011 and was a key player in the Indian e-commerce logistics industry. It was ranked number one in terms of the number of shipments handled. The brainchild of Sahil Barua and Suraj Saharan, Delhivery began as a last-mile delivery partner of restaurants in Gurugram and, over the years, grew along with the e-commerce boom in India. The case provides a detailed note of Delhivery's evolution from 2011 to 2019, especially focusing on the multifaceted development of Delhivery not limited to e-commerce delivery but also its initiative in building an ecosystem for e-commerce firms to operate in India. The competition was intensifying in the e-commerce logistics industry, and Delhivery was contemplating how it should sustain its competitive advantage, contain its losses and break-even at the earliest.